IDENTIFIKASI KUALITAS AIR BERDASARKAN SIFAT FISIK AIR SUNGAI SIAK PEKANBARU - Syech, Riad; Emrinaldi, Tengku; Simbolon, Lundu F (Komunikasi Fisika Indonesia, 2016)
A study concerning the determination of the quality of river water and well water around the river Siak using the experimental method has been investigated. This research was conducted by measuring the electrical properties of water at a temperature of 20 ÌC. The type of water used were water streams, water dug wells and water wells drilled in obtaining seven points. Measurement of the electrical properties of water was done by using multitester associated with power suppy, the plate of Copper (Cu) and Zinc (Zn) as a conductor, and the glass beaker as a container for the sample. The measurement will show voltage and current values. Based on voltage and current values,theycan calculate the value of the electrical properties of each sample. Results of river water has a resistance value of 2255.46 Î©, resistivity of 213.14 Î©m, conductivity of 0.00530(Î©m)-1, and power of 3.81 x 10-5 W. The electrical properties of best water wells dug well is six with a resistance value of 3136.46 Î©, resistivity 296.39 Î©m, conductivity of 0.00345 (Î©m)-1, and power of 7.85 x 10-5 W. Based on the results, the value of the electrical properties of the best water is the average electrical properties of water well three (drilled wells) with a resistance value of 3538.61 Î©, the electrical resistivity value of 334.39 Î©m, the electrical conductivity value of 0.00341 (Î©m)-1, and electric power of 4,76x10-5W. The water is suitable for consumption having a resistivity of 3x103 Î©, and the electrical conductivity of (300 to 500) x10-6 (Î©m)-1. Based on the standard resistivity and electrical conductivity, the river and well water samples are unfit for human consumption because the values are still far from the exposure limits.